The Gloss as Intellectual History: The Ḥāshiyahs on al-Kashshāf - Saleh, Walid A. (Oriens, 2013)
This article charts the complex reception history of the Qurʾān commentary of az-Zamakhsharī, al-Kashshāf. This commentary became the textbook used to teach tafsīr in the madrasas of the Islamic world and a large number of glosses (ḥawāshī) were written on this work. The problem so far has been that we are unable to judge or study these glosses because we lack any criteria to measure their significance and their use in the medieval tradition. This article uses three documents to offer our first attempt at ranking and clarifying the significance of the most important glosses written on al-Kashshāf.